2008
DOI: 10.1128/aem.00963-08
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a Glycerol Utilization Pathway for Amino Acid Production by Corynebacterium glutamicum

Abstract: The amino acid-producing organism Corynebacterium glutamicum cannot utilize glycerol, a stoichiometric by-product of biodiesel production. By heterologous expression of Escherichia coli glycerol utilization genes, C. glutamicum was engineered to grow on glycerol. While expression of the E. coli genes for glycerol kinase (glpK) and glycerol 3-phosphate dehydrogenase (glpD) was sufficient for growth on glycerol as the sole carbon and energy source, additional expression of the aquaglyceroporin gene glpF from E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 54 publications
(62 reference statements)
3
78
0
2
Order By: Relevance
“…C. glutamicum cannot utilize glycerol, a stoichiometric by-product of biodiesel production. By heterologous expression of Escherichia coli glycerol utilization genes, C. glutamicum was engineered to grow on glycerol [167]. The engineered strains were able to produce glutamate efficiently as well as lysine.…”
Section: Utilization Of Alternative Substratesmentioning
confidence: 99%
“…C. glutamicum cannot utilize glycerol, a stoichiometric by-product of biodiesel production. By heterologous expression of Escherichia coli glycerol utilization genes, C. glutamicum was engineered to grow on glycerol [167]. The engineered strains were able to produce glutamate efficiently as well as lysine.…”
Section: Utilization Of Alternative Substratesmentioning
confidence: 99%
“…Pyruvate carboxylase has been shown to be indispensable under detergent triggered production conditions (Peters-Wendisch et al, 2001) and vice versa under biotin limiting conditions PEPcarboxylase is responsible for anaplerosis (Sato et al, 2008, Delaunay et al, 2004, Lapujade et al, 1999. C. glutamicum was engineered for glycerol utilization by expression of the genes for glycerol facilitator, glycerol kinase, and glycerol-3-phosphate dehydrogenase from E. coli (Rittmann et al, 2008). Under ethambutol triggered L-glutamate production conditions recombinant C. glutamicum showed reduced Lglutamate yields from glycerol compared to glucose, 0.11 g g -1 compared to 0.20 g g -1 , respectively (Rittmann et al, 2008).…”
Section: Amino Acidsmentioning
confidence: 99%
“…C. glutamicum was engineered for glycerol utilization by expression of the genes for glycerol facilitator, glycerol kinase, and glycerol-3-phosphate dehydrogenase from E. coli (Rittmann et al, 2008). Under ethambutol triggered L-glutamate production conditions recombinant C. glutamicum showed reduced Lglutamate yields from glycerol compared to glucose, 0.11 g g -1 compared to 0.20 g g -1 , respectively (Rittmann et al, 2008). Production of L-lysine, which is used as a feed additive, is also carried out with C. glutamicum , Eggeling & Bott, 2005.…”
Section: Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…FDHs can be found in prokaryotic micro-organisms such as aerobic methylotrophs and chemoautotrophs, anaerobic or facultative anaerobic bacteria, as well as methanogenic archaea (Friedebold & Bowien, 1993;Jormakka et al, 2002;Karzanov et al, 1991;Schauer et al, 1986). Depending on the type of FDH, the electrons are transferred to an acceptor such as NAD Wendisch et al, 2006a, b) and has also been engineered for production of amino-acid-derived products, alcohols and organic acids from glucose and other carbon sources (Blombach et al, 2011;Buschke et al, 2011;Gopinath et al, 2011;Litsanov et al, 2012a, b;Niimi et al, 2011;Rittmann et al, 2008;Sasaki et al, 2009;Schneider et al, 2011Schneider et al, , 2012Stäbler et al, 2011). In initial experiments on the use of different carbon sources by this organism, we observed that C. glutamicum ATCC 13032 could consume formate.…”
Section: Introductionmentioning
confidence: 99%